TRANSLOKASI MERKURI (HG) PADA DAUN TANAMAN BAYAM DURI (AMARANTHUS SPINOSUS L) DARI TANAH TERCEMAR - Irsyad, Muhammad; Sikanna, Rismawaty; Musafira, Musafira (Univ. Tadulako, 2014)
Research about mercury translocation (Hg) into the leaf of Amaranthus Spinosus L from polluted soil has been carried out. The research aim was to know influences of remediation time on the abilty of mercury absorptions , knowing the concentration of mercury distribution in the leaf of A. spinosus L and abilty of A. spinosus L as hyperacumulator plant to the mercury. Remediation times used 14 days, 21 days and 42 days. The consentration of Mercury on the growth medium were 25 ppm, 50 ppm, 75 ppm, and 100 ppm. The result showed that the time of maximum absorptions were at remediation times of 14 days by mercury acumulation of 70.6901 mg/kg DM (Dry Measure). This value indicated that A. spinosus L. is hyperacumulator to the mercury and it have a potential as phytoremediator on the area that contaminated by mercury.